Test: Algebraic expressions I - Normal

Double click on maths expressions to zoom
Question 1:   Expand and simplify: ( x-2 )( x+3 )=...
x 2 +x-6
x 2 +5x-6
x 2 +2x-6
x 2 +x+6
Question 2:   Expand and simplify: ( x-1 )( x-1 )=...
x 2 -4x+1
x 2 -2x+1
x 2 -x+1
x 2 -1
Question 3:   Simplify 3 x 2 x 5 ( y-1 ) x 3 =...
3 x 4 ( y-1 ) x 3
3 x 7 y-1
3 x 4 y-1
3 x 7 ( y-1 ) x 3
Question 4:   Simplify: ( 12 x 5 y 3 ) 0 =...   for x0 and y0 .
12 x 5 y 3
0
1
144 x 10 y 6
Question 5:   Simplify: ( 2 x 3 y 2 x 2 ) 2 =...
4 x 2 y 4
4 x 6 y 4
4 x 8 y 4
2 x 4 y 6
Question 6:   Simplify: ( x-3 ) ( x-3 ) -2 =...
1 x 2 -9
1 x-3
1 ( x-3 ) 2
x 2 -6x+9
Question 7:   Simplify: x 2 -2x-8 x 2 +4x+4 =...
1 x+2
x-4 x+2
x+2 x-2
1
Question 8:   Simplify: x 3 ( x-2 )÷ ( x-2 ) 2 =...
x 3 x-2
x 3 ( x-2 )
x 3 ( x-2 ) 3
x 3 ( x-2 ) 2
Question 9:   Simplify: x 2 -16x+64 x-8 =...
1
1 ( x-8 ) 2
x-8
1 x-8
Question 10:   Factorise: 8 x 3 -1=...
( 2x-1 )( 4 x 2 +2x+1 )
( 2x-1 )( 4 x 2 -2x+1 )
( 2x-1 )( 4 x 2 -4x+1 )
( 2x-1 )( 4 x 2 +4x+1 )